Encyclopedia of Radicals in Chemistry, Biology and Materials 2012
DOI: 10.1002/9781119953678.rad081
|View full text |Cite
|
Sign up to set email alerts
|

Spin Labels and Spin Probes

Abstract: The electron paramagnetic resonance (EPR) parameters of a free radical depend strongly on its microenvironment and stable radicals can be used as reporter molecules for the EPR probing of various chemical and biological systems. Nowadays, nitroxides and trityl radicals are the most important spin labels or spin probes and their use in various applications, spin labeling, spin trapping, oximetry, pH measurement, evaluation of redox status, interactions in supramolecular systems, and so on, are examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 469 publications
0
8
0
Order By: Relevance
“…In the past few years, EPR spectroscopy has also been used as an additional tool to explore the binding properties of CB [n] with paramagnetic molecules, containing one or several nitroxide moieties as probes. [9][10][11][12][13][14][15][16][17][18][19][20] Lucarini first showed that TEMPO can be complexed by CB [7] (K a ∼ 25 ± 2 × 10 3 M −1 ), 15 the free and complexed radical exchanging slowly on the EPR time scale, and the latter showing smaller nitrogen hyperfine splitting and larger g factor values (Δa N = 0.11 mT, Δg = 0.0008). Kaifer et al 16 showed that the TEMPO moiety of 4-amido-2,2,6,6-tetramethylpiperidine-1-oxyl)cobaltocenium is engulfed in CB [8] to form a very stable inclusion compound (K a = 2.1 ± 1 × 10 8 M −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, EPR spectroscopy has also been used as an additional tool to explore the binding properties of CB [n] with paramagnetic molecules, containing one or several nitroxide moieties as probes. [9][10][11][12][13][14][15][16][17][18][19][20] Lucarini first showed that TEMPO can be complexed by CB [7] (K a ∼ 25 ± 2 × 10 3 M −1 ), 15 the free and complexed radical exchanging slowly on the EPR time scale, and the latter showing smaller nitrogen hyperfine splitting and larger g factor values (Δa N = 0.11 mT, Δg = 0.0008). Kaifer et al 16 showed that the TEMPO moiety of 4-amido-2,2,6,6-tetramethylpiperidine-1-oxyl)cobaltocenium is engulfed in CB [8] to form a very stable inclusion compound (K a = 2.1 ± 1 × 10 8 M −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Only in the last decade, many monographs, book chapters, and reviews were published regarding the physicochemical features of these radicals, methods of their synthesis, and their various applications [ 2 , 3 , 4 , 5 ] in synthetic organic chemistry (as oxidants) [ 6 ], the creation of functional materials [ 7 , 8 , 9 , 10 ], and polymer chemistry [ 11 ], including their role as agents in nitroxide-mediated radical polymerization [ 12 , 13 , 14 ], as unique molecular spin probes [ 15 ] and indispensable spin labels [ 16 , 17 ], and antioxidants and potential therapeutic agents for biological research and medicine [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of host•guest chemistry, the guests are almost exclusively [11] the radicals, and they are included in macrocyclic hosts. Several reviews [12][13][14] have already documented host•guest complexes featuring free radicals and several families of hosts including calixarenes, cyclodextrins, and cucurbiturils. This latter family of pumpkin-shape macrocycles [15][16][17][18][19] possess unique properties, in a broader context, such as ultrahigh binding [20,21], gas adsorption [22], or drug encapsulation and release [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Since CB[n] are almost exclusively soluble in water, nitroxide guest recognition is monitored using EPR by comparing the spectrum of the radical alone to that in the presence of the host in aqueous solutions. Often, a contraction of the spectrum is observed as a result of the guest experiencing a more hydrophobic environment upon inclusion in CB[n] (reduced nitrogen coupling constant a N ), and the high-field line is broadened due to reduced tumbling (i.e., reduced mobility because of a larger molecular weight) [12][13][14]26]. This way, inclusion of the nitroxide function carrying the single-electron in the host cavity is believed to be important to obtain significant changes in EPR spectra.…”
mentioning
confidence: 99%